Isolation of Campylobacter fetus subsp. jejuni from migratory waterfowl. - Luechtefeld, N A (1980)
Since the sources from which humans acquire Campylobacter enteritis are only partially known, we studied the frequency of carriage of Campylobacter fetus subsp. jejuni in migratory waterfowl. Cecal contents of various species of wild ducks were cultured on selective media that contained antibiotics to inhibit normal flora. Thirty-five percent of the 445 ducks cultured harbored C. fetus subsp. jejuni. Migratory waterfowl are yet another reservoir for this enteric pathogen and may be of public health importance for humans in the contamination of water or when used as food.